2010
DOI: 10.1002/app.32182
|View full text |Cite
|
Sign up to set email alerts
|

Rheological studies on energetic thermoplastic elastomers

Abstract: Energetic thermoplastic elastomers containing energetic groups, such as azido, nitrato, nitro, and so forth, are emerging as attractive binder systems for advanced solid rocket propellants. Poly[3,3-bis(Azidomethyl) oxetane (BAMO)-co-3-azidomethyl-3-methyl oxetane (AMMO)] comprising hard crystalline BAMO segment and the soft/amorphous AMMO segment in various molar ratios (80 : 20, 50 : 50 and 20 : 80) were synthesized during the present work. The homo polymers namely Poly-BAMO and Poly-AMMO were also synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…Energetic thermoplastic elastomers (ETPEs) have attracted much attention in the field of propellant recently for their high energetic performances, excellentm echanicalp roperties, and good processing properties amongst others [1][2][3]. As one of the most valuable ETPEs, poly(3,3-bisazidomethyl oxetane/3-azidomethyl-3-methyl oxetane) [P(BAMO/ AMMO)] has been in research focus in recenty ears [4][5][6][7][8].I t is the preferred ETPE for next-generation energetic binder [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Energetic thermoplastic elastomers (ETPEs) have attracted much attention in the field of propellant recently for their high energetic performances, excellentm echanicalp roperties, and good processing properties amongst others [1][2][3]. As one of the most valuable ETPEs, poly(3,3-bisazidomethyl oxetane/3-azidomethyl-3-methyl oxetane) [P(BAMO/ AMMO)] has been in research focus in recenty ears [4][5][6][7][8].I t is the preferred ETPE for next-generation energetic binder [2].…”
Section: Introductionmentioning
confidence: 99%
“…
1IntroductionEnergetic thermoplastic elastomers (ETPEs) have attracted much attention in the field of propellant recently for their high energetic performances, excellentm echanicalp roperties, and good processing properties amongst others [1][2][3]. As one of the most valuable ETPEs, poly(3,3-bisazidomethyl oxetane/3-azidomethyl-3-methyl oxetane) [P(BAMO/ AMMO)] has been in research focus in recenty ears [4][5][6][7][8].I t is the preferred ETPE for next-generation energetic binder [2].Twom ethods have been proposedt op repare P(BAMO/ AMMO) ETPEs, including living polymerization (see Scheme 1) to form and obtain BAMO-AMMO-BAMOt riblock copolymer and linking of two polymer blocks.Z hang et al preparedt he BAMO-AMMO-BAMO triblock copolymer through cationic ring-opening polymerization (CROP) [9][10][11]. The other method is consistent with the polyurethane syntheticp rocess (see Scheme 2).
…”
mentioning
confidence: 99%
“…139 The common disposal mechanism of poultry feathers is in landfills and the chemical resistive properties of keratin due to its a-helix and b-sheet structural packaging makes their biodegradation very slow; creating environmental concerns. 140,141 Recently, efforts have been made to create applications for chicken feathers in biobased materials such as polymer composites [142][143][144] and pyrolyzed products for hydrogen adsorption/catalytic applications. 145,146 Senoz et al 147 have reported the effective fabrication of carbon fibers from the pyrolysis of chicken feathers.…”
Section: Poultry Productsmentioning
confidence: 99%
“…Thereafter, many other energetic polymers came into light, which contained thermally labile functional groups, such as azide, nitro, and difluoroamine . Examples of such energetic polymers are poly(glycidyl azide), poly(glycidyl nitrate), poly(3‐nitratomethyl‐3‐methyloxetane), and poly(3‐difluoroaminomethyl‐3‐methyloxetane) . In addition to the mentioned labile functionalities, tetrazoles are also popular since they decompose easily with the release of large amounts of nontoxic gases, i.e ., nitrogen, the weight content of which in the parent heterocycle is 79%.…”
Section: Introductionmentioning
confidence: 99%